Pendidikan Karakter dalam Sastra Lisan Papua - Siswanto Siswanto (Balai Bahasa Provinsi Papua, 2019)
Now the condition of society badly. Dispute, killing, social discrepancy, robbery, corruption, sexual despising, deception, and slanders occur wherever. Concerned to that society condition growing spirit for studying its reasong and looking for its solution. Its ending is the same perception to do characters education. The literary work has the good education values as charactes education hope. The variety of character education in Papua oral tradition will be discuss in this papers.